Conservação de pêssegos 'Aurora-1' armazenados sob refrigeração - Cunha Junior, Luis Carlos; Durigan, Maria Fernanda Berlingieri [UNESP]; Mattiuz, Ben-Hur [UNESP] (My University, 2010)
This work aimed to evaluate the postharvest of peaches cv. Aurora-1 stored under refrigeration. The fruit were harvested in two stages (mature green and ripe). The lots were stored at three temperatures (2°C, 6°C, and 12°C), for 35 days and evaluated every seven days for skin color, loss of fresh mass (PMF), firmness (FIR), appearance, titratable acidity (TA), soluble solids (SS), soluble sugar (AS) and reducers (AR), soluble (SP) and total (PT) pectin, and the percentage of pectin solubilization (SOL). The lower storage temperature gave the greatest shelf life and the fruit at mature green stage had better appearance. The PMF showed a gradient of weight loss due to the increase of temperature and the mature green fruit had smaller weight loss at the end of storage for all temperatures, compared to mature. The skin color of the fruit mature green, stored at 2°C, had little change, from green-yellow to light yellow, while on temperatures at 6°C and 12°C this gradient was more intense. The same effect was found in ripe peaches. The FIR was affected by temperature, and the lowest temperature changed slowly. The AT for ripe peaches was higher for the mature green. There was no influence of treatments on the contents of SS, AS and AR. Peaches 'Aurora-1' showed no chilling injury symptoms and the ones harvested at mature green stage, when stored at 2°C had 35 days of shelf life.
Preservation of 'Aurora-1' peaches stored under refrigeration
Keywords: Cold storage; Harvest stage; Prunus persica